Pergeseran Makna Tradisi Punjungan Dan Jagong Dalam Konsep Walimatul ‘Urs Pada Masyarakat Gunungkidul - Muharram, Rizka Rahmawati (Mahkamah : Jurnal Kajian Hukum Islam, 2025)
This research aims to explore the meaning of the punjungan and jagong traditions in the community of Gunungkidul, which will then be examined through the concept of walimatul ‘urs in Islam. This is an empirical study with a field research approach, meaning data collection through interviews and observations, and utilizing a qualitative, descriptive-analytic approach. The author will engage in dialogue with community leaders, religious leaders, and several people from Gunungkidul. The findings show that the punjungan and jagong traditions have become practices that are deeply embedded in the community. Several aspects highlighted in both traditions include the community's excessive behavior when organizing a walimatul ‘urs, which deviates from the guidelines set by Prophet Muhammad SAW regarding walimah. The punjungan, which was initially meant to express gratitude, is now viewed as a business opportunity to seek profit, as it is hoped that those who attend will contribute more money in the form of jagong. However, despite these issues, both traditions still have positive aspects, such as fostering a sense of mutual cooperation and compassion among the people of Gunungkidul.